Kurangnya Pemahaman Tentang Konsep Dasar Ilmu Sosial Di Jenjang Sekolah Menengah - Sofi Ayu Nur Martasari; Bagus Setiawan; Sevina Yushinta Anjani (Pusat Riset dan Inovasi Nasional, 2024)
Lack of understanding of basic social science concepts at secondary school level is a serious challenge in developing students' knowledge and skills in society, nation and state. The basic concepts of social science, which include aspects such as social processes, social interaction, and social contact, are an important foundation in Social Sciences (IPS) in schools. The interdisciplinary approach to social studies covers various points of study, such as basic concepts of sociology, history, geography, economics, anthropology and political science. However, along with the complexity of the material, there are factors that cause students' lack of understanding of basic social science concepts at the secondary school level. Causative factors include teaching methods that are less effective, such as using only discussion methods without adequate explanation of the material.